Enhanced Piezo‐Photoelectric Catalysis with Oriented Carrier Migration in Asymmetric Au−ZnO Nanorod Array. Issue 18 (9th April 2020) - Xiang, Deli; Liu, Zhirong; Wu, Mengqi; Liu, Huanhuan; Zhang, Xiaodi; Wang, Zhuo; Wang, Zhong Lin; Li, Linlin
Abstract: Current photocatalytic semiconductors often have low catalytic performance due to limited light utilization and fast charge carrier recombination. Formation of Schottky junction between semiconductors and plasmonic metals can broaden the light absorption and facilitate the photon‐generated carriers separation. To further amplify the catalytic performance, herein, an asymmetric gold‐zinc oxide (Asy‐Au−ZnO) nanorod array is rationally designed, which realizes the synergy of piezocatalysis and photocatalysis, as well as spatially oriented electron−hole pairs separation, generating a significantly enhanced catalytic performance. In addition to conventional properties from noble metal/semiconductor Schottky junction, the rationally designed heterostructure has several additional advantages: 1) The piezoelectric ZnO under light and mechanical stress can directly generate charge carriers; 2) the Schottky barrier can be reduced by ZnO piezopotential to enhance the injection efficiency of hot electrons from Au nanoparticles to ZnO; 3) the unique asymmetric nanorod array structure can achieve a spatially directed separation and migration of the photon‐generated carriers. When ultrasound and all‐spectrum light irradiation are exerted simultaneously, the Asy‐Au−ZnO reaches the highest catalytic efficiency of 95% in 75 min for dye degradation. It paves a new pathway for designing unique asymmetric nanostructures with the synergy of photocatalysis and piezocatalysis. Abstract : An asymmetric Au−ZnO nanorod array is developed for efficient separation of photon‐generated charge carriers with assistance of piezophototronic effect. The unique asymmetric structure can significantly enhance the spatially directed migration and separation of the photon‐generated carriers with assistance of piezophototronic effect, and further realize enhanced catalytic activity by the synergy of piezocatalysis and photocatalysis.